Ways to Reduce In-Hospital Mortality in Patients with Cardiogenic Shock in Acute Coronary Syndrome - G. V. Artamonova; V. Yu. Kheraskov; E. V. Grigoryev; O. V. Kushch; D. V. Kryuchkov; L. S. Barbarash (Общая реаниматология)
Objective: to analyze a medical care system for acute coronary syndrome (ACS) in a large city in terms of in-hospital cardiogenic shock mortality risk management. Materials and methods. The health care facility management system for a risk for cardiogenic shock (CS) and its poor outcome (death) was a methodological basis of this study. The information from case histories of ACS patients consecutively admitted to the Kemerovo Cardiology Dispensary (Kemerovo, Russia) in the period 2006 to 2011 was used to develop an electronic database. Sampling included 19281 patients with ACS, 6537 with myocardial infarction (MI), 493 with CS. Results and discussion. The medical care system for patients with ACS encompasses an emergency team (a prehospital level), a specialized cardiac hospital (an in-hospital level) with a multistage therapeutic and diagnostic process in relation the severity of a patient’s status. The management is based on the principle of continuity of care, by applying the well-defined activity algorithms through valid information exchange and risk stratification for poor outcomes of ACS. An antishock team working just in the admission unit of a hospital was set up to treat high CS risk patients. A systems approach allowed the strategy of early specialized medical care to be developed with a priority of primary percutaneous coronary interventions (PCI) as reperfusion therapy in patients with ST-elevation MI. In 2006-2011, every three patients with suspected ACS had verified MI that was com_ plicated by CS in 7.5%. In the CS group, the in-hospital mortality rates totaled 88.0% of cases; that after primary Адрес для корреспонденции (Correspondence to): PCI was 62.2%. In the examined period, the introduction of innovation clinical and organizational approaches provided a reduction in this indicator by 17.6 and 37.5%, respectively. Conclusion. The efficiency of risk management for CS and its poor outcomes in patients with ACS is determined by the unique principles of medical care rendering at all levels on the basis of risk management methodology.